Arabidopsis NPF4.6 and NPF5.1 Control Leaf Stomatal Aperture by Regulating Abscisic Acid Transport - Shimizu, Takafumi (Genes (Basel), 2021)
The plant hormone abscisic acid (ABA) is actively synthesized in vascular tissues and transported to guard cells to promote stomatal closure. Although several transmembrane ABA transporters have been identified, how the movement of ABA within plants is regulated is not fully understood. In this study, we determined that Arabidopsis NPF4.6, previously identified as an ABA transporter expressed in vascular tissues, is also present in guard cells and positively regulates stomatal closure in leaves. We also found that mutants defective in NPF5.1 had a higher leaf surface temperature compared to the wild type. Additionally, NPF5.1 mediated cellular ABA uptake when expressed in a heterologous yeast system. Promoter activities of NPF5.1 were detected in several leaf cell types. Taken together, these observations indicate that NPF5.1 negatively regulates stomatal closure by regulating the amount of ABA that can be transported from vascular tissues to guard cells.